1997
DOI: 10.1002/(sici)1097-4628(19971121)66:8<1507::aid-app11>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Citrate esters as plasticizers for poly(lactic acid)

Abstract: Citrate esters were used as plasticizers with poly(lactic acid) (PLA). Films were extruded using a single-screw extruder with plasticizer contents of 10, 20, and 30% by weight. All of the citrate esters investigated were found to be effective in reducing the glass transition temperature and improving the elongation at break. It was observed that the plasticizing efficiency was higher for the intermediate-molecularweight plasticizers. Hydrolytic and enzymatic degradation tests were conducted on these films. It … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
293
0
5

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 429 publications
(312 citation statements)
references
References 2 publications
14
293
0
5
Order By: Relevance
“…Labrecque et al [19] studied the effect of plasticizers on the thermal properties of PLA and they have found that all plasticizers were miscible with PLA. The reason for good solubility of PLA in citrate plasticizers is due to the polar interactions between the ester groups of PLA and the plasticizer [20] .…”
Section: Differential Scanning Calorimetry (Dsc)mentioning
confidence: 99%
See 1 more Smart Citation
“…Labrecque et al [19] studied the effect of plasticizers on the thermal properties of PLA and they have found that all plasticizers were miscible with PLA. The reason for good solubility of PLA in citrate plasticizers is due to the polar interactions between the ester groups of PLA and the plasticizer [20] .…”
Section: Differential Scanning Calorimetry (Dsc)mentioning
confidence: 99%
“…Thus, good miscibility between PLA and plasticizers is essential. Various plasticizers, which have been proved as effective plasticizers for PLA, citrate esters are used as plasticizers with a variety of different polymers such as poly (methyl methacrylate) [18] and cellulose acetate [19] . They are nontoxic and approved for use as additives in food, personal care products, and in medical plastics [18] .…”
Section: Introductionmentioning
confidence: 99%
“…In this paper TBC, as plasticizer, was added to the PLLA, PPC and PVAc, with the purpose of decreasing its glass transition temperature and improving their miscibility. PLLA is miscible with low molecular weight plasticizers like glycerol [23] , triactine [24] and low molecular weight citrates [25] . The aim of this work was to investigate the newly developed blends of PLLA and PPC with additives (PHB, PVAc and TBC).…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8] ment of the flexibility could also be achieved by blending it with low-molecular-weight plasticizers such as citrate esters, polyethylene glycol, polypropylene glycol, and oligomeric lactic acid. [9][10][11][12][13][14][15][16] Epoxidized soybean oil (ESO) is used as a plasticizer for PLA by increasing the elongation at break of the polymer and as well as depressing the glass transition temperature of the plasticized PLA. Carbon nanotubes (CNTs) have received much attention because of their fascinating properties, such as high modulus and high electrical/thermal conductivity.…”
mentioning
confidence: 99%